Dr. Caner Kaçmaz — Deep Plane Facelift — Istanbul - Kaçmaz, Caner (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Caner Kaçmaz, practicing in Istanbul, Turkey. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003328; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; turkey; istanbul